Industrial brushless servomotors - Moreton, Peter
Industrial use of the brushless servomotor, for instance in robotics, is increasing rapidly, because of their low maintenance needs and capabilities at high transient speeds. They offer flexibility and high performance, and advances in power electronics and microelectronics means they are now more affordable. This handbook gives the user of brushless servomotors a comprehensive guide to their use, including a description of all main features of the brushless motor drive system. Throughout mathematics is kept to a minimum and practical guidance is given based on real-life experience. Peter Moreton is a Research Fellow at the University of Bristol, having spent time in industry and universities worldwide. Written by a respected expert in the field - Peter Moreton has both high level academic and industrial experience Indispensible guide to a rapidly growing new area of technology Concise and accessible with a minimum of maths.